Survei Kepuasan Masyarakat terhadap Pelayanan Posyandu di Daerah Bekasi - Suwandi Suwandi; Muhammad Rangga Aldjudin (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
This study aims to determine the level of community satisfaction with Posyandu services in the Bekasi area. Posyandu, as the frontline of community health services at the village level, plays an important role in monitoring the growth and development of toddlers, providing immunization services, and delivering health education. The method used in this study was a quantitative survey, with questionnaires distributed to 150 respondents who were users of Posyandu services in several subdistricts in Bekasi. The aspects evaluated include service quality, facility availability, staff attitude, and the effectiveness of the information provided. The survey results indicate that the majority of respondents are satisfied with the services provided, although there are some notes regarding limitations in facilities and service hours that need to be improved. These findings are expected to serve as input for Posyandu managers and local governments in enhancing the quality of community health services at the grassroots level.